Ventilator Portable Sebagai Alat Bantu Pernapasan Pada Penanganan Pasien COVID-19 - Florentina Victorya Liwun; Muhammad Fattah Hafri Taqwandi; Aulia Arba Chinta Ramadhani; Widhy Ananda; Mauludin Mauludin; Andry Fitrian (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2021)
Coronavirus is a type of virus that attacks the respiratory tract. Some people with COVID-19 are showing symptoms and some are not showing symptoms. Common symptoms include runny nose, cough, sore throat, fever, and shortness of breath. This condition gets worse if the infected patient has a history of congenital disease. This virus will spread quickly through the intermediary of droplets from saliva and nose. In the condition of patients who have difficulty breathing, a ventilator is needed to help supply oxygen to the lungs. The purpose of this study was to make a portable ventilator as a breathing apparatus for handling COVID-19 patients. The stages of implementing this research are carried out in a blended manner, namely online during the preparation stage, the design stage of the tool design and offline at the tool making stage, testing and evaluating the tool. From the results of the design and stages of the testing process, this portable ventilator can efficiently assist breathing work in patients experiencing shortness of breath such as COVID-19 patients because the working system of this device is to supply oxygen to the lungs through a breathing tube according to the patient's needs.